Mutu Layanan Taman Pendidikan Al Quran (TPQ) di Era Modern: Service Quality TPQ Daarut Taubah - Lirizki, Riza (STID Al-Hadid, 2025)
SERVICE QUALITY OF QURANIC EDUCATION CENTERS (TPQ) IN THE MODERN ERA: SERVICE QUALITY AT TPQ DAARUT TAUBAH. Service quality is an essential aspect in ensuring the sustainability and effectiveness of da'wah institutions, including Qur'anic education centers (TPQ). This study aims to analyze the service quality of the Daarut Taubah Quranic Education Center (TPQ), located in the former Dolly red-light district of Surabaya, using service quality (SERVQUAL) approach. The SERVQUAL model is employed to evaluate service quality across five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The study adopts a qualitative-descriptive approach, with data collected through Focus Group Discussions (FGDs) involving five TPQ Daarut Taubah students and field observations. The findings reveal that, in general, the services at TPQ Daarut Taubah meet students’ expectations in terms of responsiveness and assurance. However, gaps remain in the dimensions of tangibles, reliability, and empathy. These gaps include issues related to cleanliness and infrastructure, the punctuality of instructors, and a lack of attention to students’ non-academic needs. Despite these shortcomings, the instructors are considered competent, polite, responsive to student concerns, and capable of creating a safe and comfortable learning environment. The study concludes that improvements are needed in the areas where service gaps exist to enhance the overall service quality of TPQ Daarut Taubah.